2007
DOI: 10.1080/10245330701383700
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone mineral density in children with hemophilia: Mansoura University children hospital (MUCH) experience, Mansoura, Egypt

Abstract: (1) Early detection of osteopenic hemophilic children using DEXA scanning, (2) bisphosphonates plus calcium for hemophilic children with reduced BMD, (3) evaluation of the effect of on demand vs. prophylaxis replacement therapy in hemophilic patients on BMD and hemophilic arthropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 13 publications
3
37
0
3
Order By: Relevance
“…Decreased BMD has been previously demonstrated in children with haemophilia, but only using measures of areal BMD assessed by DXA (mean Z‐scores for lumbar spine aBMD −1.6 [4], −0.9 [2] and −0.7 [19]). This areal BMD is a general indicator of the bone mass, while information is lacking about the bone structure and geometry.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased BMD has been previously demonstrated in children with haemophilia, but only using measures of areal BMD assessed by DXA (mean Z‐scores for lumbar spine aBMD −1.6 [4], −0.9 [2] and −0.7 [19]). This areal BMD is a general indicator of the bone mass, while information is lacking about the bone structure and geometry.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with haemophilia seem to achieve lower peak bone mineral mass when compared to healthy controls. In favour of this hypothesis, studies showed reduced bone mineral density among children with severe haemophilia (Barnes, 2004, Abdelrazik , 2007., Nair, 2007., Tlacuilo-Parra, 2008. The major impact on bone formation during childhood and adolescents has physical activity and, moreover, weight-bearing exercises.…”
Section: Physical Activitymentioning
confidence: 96%
“…The strong relationship has been established between reduced bone mass and joint status in young patients with haemophilia (Abdelrazik, 2007), as well as among adult haemophiliacs (Nair, 2007., Katsarou, 2009. Joint status was evaluated using clinical score as described by the Orthtopedic Advisory Council of the World Federation of Haemophilia (RodriguezMerchan EC, 2003.…”
Section: Joint Status and Prophylactic Therapymentioning
confidence: 99%
“…Joint disease reduces physical fitness and muscular strength, creates muscle atrophy, and in a vicious cycle exacerbates articular instability and repeated bleeding episodes. Children with hemophilia may have reduced bone mineral density compared to age- and gender-matched controls 27. Hemarthroses begin in the toddler age.…”
Section: Prophylaxis In Nonrandomized Studiesmentioning
confidence: 99%
“…Children with severe hemophilia may have reduced bone mineral density (BMD) compared with age-matched controls,27 but prophylaxis starting in early childhood may preserve normal BMD and reduce the risk of degenerative bone disease, pathologic fractures, and the financial burden that such problems impose 80…”
Section: Consideration Of Cost In Hemophilia Prophylaxismentioning
confidence: 99%